2018
DOI: 10.3390/ijms19072138
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endocytosis in the Transdermal Penetration Mechanism of Ketoprofen Nanoparticles

Abstract: We previously designed a novel transdermal formulation containing ketoprofen solid nanoparticles (KET-NPs formulation), and showed that the skin penetration from the KET-NPs formulation was higher than that of a transdermal formulation containing ketoprofen microparticles (KET-MPs formulation). However, the precise mechanism for the skin penetration from the KET-NPs formulation was not clear. In this study we investigated whether energy-dependent endocytosis relates to the transdermal delivery from a 1.5% KET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 40 publications
(72 reference statements)
3
47
0
Order By: Relevance
“…We have also reported the method for preparing solid nanoparticles using bead mill treatment and showed that the addition of HPβCD and MC enhances the dispersion stability and crushing force, respectively [15,[17][18][19]. In addition, our previous studies using indomethacin showed a hydrophilic gel base, such as carbopol, provides for a high drug release of solid nanoparticles from the gel [15,[17][18][19]. Based on these findings, HPβCD, MC and carbopol were selected as components of TL-NPs-Gel in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also reported the method for preparing solid nanoparticles using bead mill treatment and showed that the addition of HPβCD and MC enhances the dispersion stability and crushing force, respectively [15,[17][18][19]. In addition, our previous studies using indomethacin showed a hydrophilic gel base, such as carbopol, provides for a high drug release of solid nanoparticles from the gel [15,[17][18][19]. Based on these findings, HPβCD, MC and carbopol were selected as components of TL-NPs-Gel in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Type SM-4 methylcellulose (MC) and 2-hydroxypropyl-β-cyclodextrin (HPβCD) were provided by Shin-Etsu Chemical Co., Ltd. (Tokyo, Japan) and Nihon Shokuhin Kako Co., Ltd. (Tokyo, Japan), respectively. The HPβCD and MC were selected to enhance the dispersion stability and crushing force, respectively [15,[17][18][19]. Mixtures of these reagents (TL powder, MC and HPβCD) were dispersed in distilled water, and zirconia beads (0.1 mm in diameter) were added.…”
Section: Preparation Of Ophthalmic Formulations Containing Tlmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism of transdermal delivery has not been thoroughly investigated [23]. While most transdermal mechanisms focused on keratin, few studies have reported the role of tight junctions [24] and cell endocytosis [25].…”
Section: Introductionmentioning
confidence: 99%